2017
DOI: 10.1111/capa.12202
|View full text |Cite
|
Sign up to set email alerts
|

Power and smart meters: A political perspective on the social acceptance of energy projects

Abstract: Social acceptance has become a key consideration for promoters, government officials and citizens when instituting new energy infrastructures and technologies. Often theorized in normative terms, it is not clear whether and when social acceptance matters. This article explores the rollout of smart meters in Quebec, which proceeded despite significant opposition from municipalities, community groups and unions. Drawing on core concepts from punctuated equilibrium theory-policy monopoly, policy venue, policy ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
(32 reference statements)
0
12
0
2
Order By: Relevance
“…Larson and Ribot, 2004). This is a matter of process legitimacy, and social legitimacy, and the analysis put forward supports the argument that both rollouts fall short on these fronts (also see Jegen and Philion, 2017). They are characterised by scalar biases that reduce the role of households as smart meter users to responsibilised recipients of socio-technical interventions, whose behaviour and everyday use of electric grids has to fall in line with decisions made at the national scale.…”
Section: Embedding Social and Technical Differentiation In The Automamentioning
confidence: 61%
“…Larson and Ribot, 2004). This is a matter of process legitimacy, and social legitimacy, and the analysis put forward supports the argument that both rollouts fall short on these fronts (also see Jegen and Philion, 2017). They are characterised by scalar biases that reduce the role of households as smart meter users to responsibilised recipients of socio-technical interventions, whose behaviour and everyday use of electric grids has to fall in line with decisions made at the national scale.…”
Section: Embedding Social and Technical Differentiation In The Automamentioning
confidence: 61%
“…However, Carlman () showed that public opinion surveys did not necessarily translate into public, political, and regulatory acceptance of renewables, such as wind power. More recently, Wüstenhagen, Wolsink and Bürer (: 2683) highlighted social acceptance as “a powerful barrier to the achievement of renewable energy targets.” As shown in Figure , they distinguished three dimensions: socio‐political acceptance , or the broadest, most general level of social acceptance of both policies and technologies by the public, key stakeholders (that is, employees) and policymakers (see also Jegen and Philion ); community acceptance , or “the specific acceptance of siting decisions and renewable energy projects by local stakeholders, particularly local residents and local authorities” (Wüstenhagen, Wolsink and Bürer : 2685), which may vary over time; and market acceptance , or the process of widespread adoption of an innovation. In particular, energy projects are embedded in complex multisided infrastructures that involve consumers, investors, and producers.…”
Section: Varieties Of Social Licensementioning
confidence: 99%
“…But no one is in any doubt that Hydro-Quebec is the key actor and that there is institutional and technological lock-in, which limits the leeway for new ideas. Up to now, the electricity monopoly around Hydro-Quebec seems to hold [60]. And it uses its key position to frame smart grid mainly as a technological fix to update the existing grid, make it safer, and improve invoicing.…”
Section: Figure 1 Degree Of Centralization Vs Decentralization In Smamentioning
confidence: 99%